(untitled) (Journal of Medical & Health Sciences Review, 2023)
The human body plays host to a vast and diverse community of microorganisms, collectively known as the microbiome. This hidden world, particularly within the gut, plays a crucial role in maintaining human health. However, disruptions in the delicate balance of these microbial communities, termed dysbiosis, can contribute to the development of various diseases. This article delves into the complex interactions between gut bacteria and various diseases, highlighting how understanding these relationships holds immense potential for future therapies and preventive strategies. Keywords: Microbiome, gut bacteria, dysbiosis, human health, disease, inflammation, metabolism, immune system